Hubungan Dukungan Sosial Terhadap Depresi Pada Lansia Di Desa Suwaluh Kecamatan Balong Bendo Kabupaten Sidoarjo - Wicaksono, Arif; Achwandi, Moch. (JURNAL KEPERAWATAN BINA SEHAT, 2017)
The number of elderly is increasing, so the elderly with various changes in both the biological, social, cultural, economic, health, and psychology of the most vulnerable groups with variety of mental and behavioral problems, namely depression. Social support can affect the incriedence of depression in the elderly. Purpose of this study was to defermined the incidence of depression in elderly on Suwaluh Village Balong Bendo District Sidoarjo. Therefore it is necessary to know whether there is social support or not, that can affect depression in elderly. This research use, a correlational analytic design with cross sectional approach. The population is all elderly which in Suwaluh Village, which is about 45 elderly, and who included in criteria to studied was 25 elderly. Data collection using support questionnaires and GDS (Geriatric Depression Scale). The results showed that elderly who get social support as many 17 respondents (68%), and who experienced mild depression as many as 12 respondents (32%). Spearman rho test result, obtain ed a value p (0,291) > α (0,005) means that Ho accepted.Results of research which states that there is no relationship of social support on depression in the elderly because it is not consistent with the theory. The presence of social support, the elderly can become depressed because think of negative things about the environment too much. Occurrence of depression experienced by the elderly could also be due to stay at home. Prolonged sadness, often moody, and does not want to socialize with friends, relatives, neighbors or other in the vicinityKeyword: Social Support, Depression, Elderly